Characterization of premalignant oral lesions diagnosed in a Stomatology service from Pinar del Río - Yamirka Aleida González Gómez; Jadier Wong Silva; Marilen López González; Dunia Milagros Labrador Falero (Medisur)
Foundation: premalignant lesions are those that present cellular alterations, generate abnormal blood cells and can affect the patient's oral tissues. They usually manifest initially in the oral cavity, or after spreading from other parts of the body through lymphatic and blood systems. Objective: to characterize premalignant oral lesions present in adult patients. Methods: descriptive, cross-sectional study, in patients belonging to the Luis Augusto Turcios Lima University Teaching Polyclinic, in the Pinar del Río municipality, from January to December 2022. From the universe made up of 5,259 patients treated in the Basic Stomatological Services consultation, a sample of 53 was taken, selected through simple random sampling. The results were represented in absolute frequencies and percentages charts, as summary measures. Results: the majority of patients with premalignant oral lesions belonged to the male sex (78.5%) and to the group aged 60 and over (58.5%). The most frequent risk factor was smoking (86.8%). Leukoplakia prevailed (69.8%), with a greater frequency of location on the lips (43.4%). The most used treatment was medication-surgical (58.5%). Conclusions: premalignant lesions of the oral cavity in the series of patients under study were characterized by their predominance in males, over 60 years of age, and smokers. Leukoplakia was the most common lesion, and the lips were the most affected site. Medication-surgical treatment was the most used.